Electronic administration and its role in activating the tasks of public relations: A field study on a sample of public relations departments in the public and private sectors in the city of Riyadh: - Bedaiwi, Nahlah Mohammed (Journal of Economic, Administrative and Legal Sciences, 2022)
The purpose of this study is to identify to what extent the public relations perform its functions through the management of electronic in public and private institutions sector.To reach the goals of the study, the researcher followed the curriculum survey of the questionnaire methodology; where the researcher collects the information required through the answer for research questions.The study population are from the departments of public relations in both sectors, public and private in the city of Riyadh.The sample in this study are the departments of public relations in both sectors, public and private, it has been taken in a manner sample class and represent 40 % of each layer in each sector, and within each layer pulled a sample in a manner sample random simple from each layer.To achieve the objectives of this study, the researcher conducted a study on two types of departments which departments of public and private administrations sectors in the city of Riyadh.The following findings are from the field survey:In the government sector, the researcher found that 57.1 % rely entirely on the electronic management in the management of public relations.It turned out during the study a differences in the activation of some functions of the electronic management; where it was found that the private sector outperform the government sector in two subjects only; first is the use of public relations management including electronic administration in the research survey of the public’s opinion, and the second is the use of public relations management including electronic administration in the campaigns of media.
Keywords: electronic management; public relations; public sectors; private sectors